The Pages of History of the Russian Federal Centre of Forensic Science of the Ministry of Justice of the Russian Federation - L. P. Morozov (Теория и практика судебной экспертизы, 2022)
The author dedicates this article to the 60th anniversary of the Russian Federal Centre of Forensic Science of the Ministry of Justice of the Russian Federation. He observes the “academic biography” of the Centre and the prerequisites for the emergence of its forensic scholarly tradition. The article also clarifies the features of the scientific school, whereby the scientific community of scientists of the Center received the status of a scientific school and the period of its occurrence.